Kaposiform hemangioendothelioma and tufted angioma - (epi)genetic analysis including genome-wide methylation profiling - Ten Broek, Roel; Koelsche, Christian; Eijkelenboom, Astrid; Mentzel, Thomas; Creytens, David; Vokuhl, Christian; van Gorp, Joost M.; Versleijen-Jonkers, Yvonne M.; van der Vleuten, Carine J.; Kemmeren, Patrick; van de Geer, Ellen; Deimling, Andreas von; et al. (Annals of diagnostic pathology, 2020)
Kaposiform hemangioendothelioma (KHE) is a locally aggressive vascular condition of childhood and is clinicopathologically related to tufted angioma (TA), a benign skin lesion. Due to their rarity molecular data are scarce. We investigated 7 KHE and 3 TA by comprehensive mutational analysis and genome-wide methylation profiling and compared the clustering, also with vascular malformations. Lesions were from 7 females and 3 males. The age range was 2 months to 9 years with a median of 10 months. KHEs arose in the soft tissue of the thigh (n = 2), retroperitoneum (n = 1), thoracal/abdominal (n = 1), supraclavicular (n = 1) and neck (n = 1). One patient presented with multiple lesions without further information. Two patients developed a Kasabach-Merritt phenomenon. TAs originated in the skin of the shoulder (n = 2) and nose/forehead (n = 1). Of the 5 KHEs and 2 TAs investigated by DNA sequencing, one TA showed a hot spot mutation in NRAS, and one KHE a mutation in RAD50. Unsupervised hierarchical clustering analysis indicated a common methylation pattern of KHEs and TAs, which separated from the homogeneous methylation pattern of vascular malformations. In conclusion, methylation profiling provides further evidence for KHEs and TAs potentially forming a spectrum of one entity. Using next generation sequencing, heterogeneous mutations were found in a subset of cases (2/7) without the presence of GNA14 mutations, previously reported in KHE and TA.
Available online 10 December 2019
Gesehen am 24.06.2020